The study on relationship between technology acceptances model (TAM) toward employees' motivation using technology at Syarikat Air Terengganu Sdn. Bhd. (SATU) / Fatimah Hafizah Mamat - Mamat, Fatimah Hafizah (Faculty of Business and Management, 2018)
This research examines the study of relationship between Technology Acceptances Models (TAM) towards employees' motivation using the technology at Syarikat Air Terengganu Sdn. Bhd, Kuala Terengganu. In this study, the independent variable is Technology Acceptances Models (TAM) consist of two elements which are Perceived of Usefulness and Perceived Ease of Use. Meanwhile, the dependent variable is employees' motivation to use technology in the organization. The questionnaires had been distributed by used a random sampling techniques to the all 86 respondents according to the Krejcie and Morgan sample size that fixed for this research and had been return without rejection from the respondents. Furthermore, the questionnaire is the combination of the closed ended with optional answer by using Likert scale item. Next, the data has been analysed by using a descriptive analysis and Pearson correlation. From the descriptive analysis result explain that the level of employees' motivation was high which present the employees are motivated. By the Pearson correlation analysis result, specifies the relationship hypothesis was accepted which there is the relationship between technology acceptances towards employees' motivation in using technology. Thus, this study provides a several recommendation that can be beneficial to the organization and future research.